Species for changing climates – Australian dryland forestry opportunities. Issue 2 (3rd April 2018) - Bush, D.; Harwood, C.; Pinkard, E.
ABSTRACT: Climate change during the next century is projected to result in increased mean annual temperatures and changes in rainfall amounts and seasonality. It will also cause often challenging effects such as droughts, storms, heatwaves and changes in pest and disease occurrence throughout Australia's current plantation estate. The direct effects of climate change are not the only foreseeable impacts on Australian plantations; competition for the current medium–high-rainfall plantation land base from agriculture and urban development, driven by both climate change and Australian and global societal trends, is also likely. Climatic conditions within most of the existing plantation estate in southern Australia are likely to become hotter, drier and more variable, and available alternative sites will most likely have dry climates. In order to sustain plantation productivity into the future, the forest industry will need to use new breeds of currently planted species or alternative species that are adapted to hotter and drier environments. In this review, we examine opportunities for establishing plantations of tree species adapted to dryland conditions, as well as trade-offs between productivity and survival in unpredictable environments. We discuss two strategies, adapting existing breeds to changing climates and identifying and domesticating novel species. Traditional timber and fibre products are considered, as well as emerging products such as sandalwood oil and services such as carbon sequestration. The need for development of policies that encourage effective and sustainable plantation expansion into dryland areas is discussed.